Pengaruh Pengelolaan Sampah Terhadap Kesadaran Lingkungan Mahasiswa Di Universitas Negeri Medan - sinaga, epelima; Hutasoit, Era Sulastri; Sitepu, Agnes Dea Lita Br; Purba, Bonaraja (Jurnal Ilmiah Wahana Pendidikan, 2025)
Environmental awareness is an important factor in maintaining the sustainability of the ecosystem, especially in the academic environment. However, the low involvement of students in waste management indicates that the level of environmental awareness still needs to be improved. This study aims to examine the effect of waste management on environmental awareness of students at Universitas Negeri Medan. This study applies a quantitative approach with a survey method, where data is collected through the distribution of a google form-based questionnaire. Data analysis uses simple linear regression to identify the relationship between independent variables and dependent variables. The results of the study indicate that waste management has a positive and significant effect on students' environmental awareness, with a regression coefficient value of 0.660 and a significance level of 0.000. This finding indicates that the more optimal the waste management system implemented, the higher the level of students' environmental awareness. The results of this study emphasize the importance of integration between environmental education, provision of adequate waste management facilities, and implementation of green campus policies to increase student awareness and participation in maintaining environmental cleanliness. Therefore, a more comprehensive approach is needed, such as educational programs and policies based on student participation, to optimize the effectiveness of waste management in the campus environment.